Analisis Pengaruh Literasi Keuangan, Pembelajaran di Perguruan Tinggi, dan Pengalaman Kerja Terhadap Perilaku Keuangan (Studi Kasus pada Alumni Mahasiswa Akuntansi 2016 Fakultas Ekonomi Universitas Islam Malang) - Moh. Mahrus Hadi; Junaidi Junaidi; Arista Fauzi Kartika Sari (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to determine the influence of financial literacy, learning in higher education and work experience on financial behavior. This research is a quantitative study. The sample of this study was a group of 100 respondents of FEB accounting student alumni Class of 2016, Islamic University of Malang. Data were analyzed using multiple linear regression analysis. Based on the results of data analysis, the results of the t-test indicate that: (1) Financial literacy has no significant effect on financial behavior. (2) Learning in higher education has no significant effect on financial behavior. (3) Work experience has no significant effect on financial behavior. Keywords: Financial literacy, learning in higher education, work experience, financial behavior